A Systematic Literature Review of Emotion Regulation Measurement in Individuals With Autism Spectrum Disorder. Issue 6 (24th October 2014) - Weiss, Jonathan A.; Thomson, Kendra; Chan, Lisa
<x xml:space="preserve">Abstract</x> Emotion regulation (ER) difficulties are a potential common factor underlying the presentation of multiple emotional and behavioral problems in individuals with Autism Spectrum Disorder (ASD). To provide an overview of how ER has been studied in individuals with ASD, we conducted a systematic review of the past 20 years of ER research in the ASD population, using established keywords from the most comprehensive ER literature review of the typically developing population to date. Out of an initial sampling of 305 studies, 32 were eligible for review. We examined the types of methods (self‐report, informant report, naturalistic observation/ behavior coding, physiological, and open‐ended) and the ER constructs based on Gross and Thompson's modal model (situation selection, situation modification, attention deployment, cognitive change, and response modulation). Studies most often assessed ER using one type of method and from a unidimensional perspective. Across the 32 studies, we documented the types of measures used and found that 38% of studies used self‐report, 44% included an informant report measure, 31% included at least one naturalistic observation/behavior coding measure, 13% included at least one physiological measure, and 13% included at least one open‐ended measure. Only 25% of studies used more than one method of measurement. The findings of the current review provide the field with an in‐depth analysis of various ER measures and how each measure taps into an ER framework. Future research can use this model to examine ER in a multicomponent way and through multiple methods. Autism Res2014, 7: 629–648. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.